CiTRUsX pomelo tissue culture for natural antioxidant enrichment in food and health products - Zarina, Zakaria, Dr.; Ku Syahidah, Ku Ismail; Khairul Farihan, Kassim; Alina Rahayu, Mohamed; Azlinda, Ali; Nor Alina, Nazri (Korea Invention Promotion Association (KIPA), 2010)
Organized by Korea Invention Promotion Association (KIPA), 3rd - 7th December 2009 at Pacific Hall, COEX, Korea.